Placement Of Teachers Based On School Needs Using Iterative Dichotomiser 3 - Wardoyono, Hengky; Sediyono, Eko; Iriani, Ade (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research aims to develop an effective teacher placement model based on school needs using the Iterative Dichotomiser 3 (ID3) algorithm. The right placement of teachers can improve the quality of education and ensure equal distribution of human resources in the school environment. The ID3 algorithm builds a decision tree that helps determine optimal teacher placement. The research results show that using ID3 in the teacher placement process can produce more structured and fair decisions, compared to traditional methods. Test and Score results in 100x experiments, with the model or method used as Tree, showing that the AUC value is 0.950. The CA value is 0.934. The F1 value is 0.93. The Precision value is 0.934. The Recall value is 0.934. It is predicted that 1 subject teacher can teach the number of students per class in class 10 around 32 people, and class 11 around 31 people, and class 12 around 37 people. It is hoped that the implementation of this model can support educational policies in improving the distribution of educational quality in various classes and subjects.